0
votes
0answers
27 views

Multiplicative Inverse of a Power Series

For a formal power series $$F(x) = \sum p_i x^i$$ a multiplicative inverse of $F$ exists iff $p_0 \neq 0$. The inverse $\sum q_i x^i$ satisfies the recursion $$q_0 =\frac{1}{p_0}\\ q_{n} = ...
0
votes
1answer
105 views

Differential Equations: Find the first four terms in each of two solutions y1 and y2 …

The differential equation is $y'' - xy' - y = 0$ with $x_0 = 1$ Now, I know how to find the recurrence relation... and it's given by: $a_(n+2) = [(a_(n+1) + a_(n)) / (n+2)]$ But I can't quite ...
1
vote
2answers
90 views

How to solve $f_{n}(x)=xf_{n-1}(x)-f_{n-2}(x)$?

How to solve the following recurrence relation $$f_{n}(x)=xf_{n-1}(x)-f_{n-2}(x)$$ with the initial conditions $f_{1}(x)=x, f_{2}(x)=x^2-1$? The answer is that ...
2
votes
3answers
1k views

Finding the explicit formula for a recursive sequence, using power series

The Task is to find the explicit expression for the given recursive sequence with the help of power series. Given: $a_{0}=0,\ a_{1}=1 \quad$ and $\quad a_{n}=5\cdot a_{n-1} -6\cdot a_{n-2}\quad $ ...
2
votes
2answers
712 views

Using Generating Functions to Solve Recursions

I have the recursion $A(n) = A(n-1) + n^2 - n$ with initial conditions $A(0) = 1$. I attempted to solve it using generating functions and I'm not quite sure I have it right, so I thought I might ask ...
0
votes
3answers
75 views

Power series and recurrence

Please help me find the radius of convergence and the value of the following power series: $\sum_{n=0}^{\infty} a_nz^n$, when $a_0=1,a_1=-1$, and $3a_n+4a_{n-1}-a_{n-2}=0$ for $n>1$.
2
votes
1answer
125 views

How can I express such function as known functions or power series?

$$\int_0^x \cfrac{1}{1+\int_0^t \cfrac{1}{2+\int_0^{t_1} \cfrac{1}{3+\int_0^{t_2} \cfrac{1}{\cdots} dt_3} dt_2} dt_1} dt =f(x)$$ $$\int_{0}^{x} \frac{1}{n+h_{n+1}(t)}{d} t=h_n(x)$$ ...
4
votes
4answers
153 views

Expansion of $x^4\over1+x^2$ into a power series

I calculated the generating function $A(x)$ of the recurrence $a_n = a_{n-2} - 2a_{n-3}$, $(n \ge 0, a_0 = a_1 = 0, a_2 = 2)$ and I have no clue on how to expand it into a power series in order to ...
14
votes
3answers
638 views

Solving a difficult recursion via generating functions

I have been trying to solve the recurrence: \begin{align*} a_{n+1}=\frac{2(n+1)a_n+5((n+1)!)}{3}, \end{align*} where $a_0=5$, via generating functions with little success. My progress until now is ...
3
votes
3answers
198 views

Recurrence relations problem (1st order, linear, constant coeff, inhomogeneous)

okay im supposed to find a recurrence relation for $$ a_{n+1}= b \cdot a_n + c \cdot n \ \ \ \ \ \ \ \ \ \ \ \ \mathbf{(1)} $$ where $b$ and $c$ are constants. the method we learned in class was ...